Simulation and Learning - Landriscina, Franco. author. aut Link
XVII, 236 p.
Keywords: This book conveys the incredible instructional potential of simulation as a modality of education and provides guidelines for the design of effective simulation-based learning environments. The framework of the book consists of model-centered learning---learning that requires a restructuring of individual mental models utilized by both students and teachers. Simulation models extend our biological capacity to carry out simulative reasoning. Recent approaches to mental modeling, such as embodied cognition and the extended mind hypothesis are also considered in the book, which relies heavily on recent advances in cognitive science. A conceptual model called the “epistemic simulation cycle” is proposed as a blueprint for the comprehension of the cognitive activities involved in simulation-based learning and for instructional design.